Acute rhabdomyolysis - Pascale de Lonlay; Asmaa Mamoune; Yamina Hamel; Michel Bahuau; Sabrina Vergnaud; Moniqu Piraud; Lætitia Lallemand; Marie-Ange Nguyen More; Mai Thao Vio; Norma Beatriz Romero (Нервно-мышечные болезни, 2015)
Rhabdomyolysis results from the rapid breakdown of skeletal muscle fibers, which leads to leakage of potentially toxic cellular contents into the systemic circulation. Acquired causes by direct injury to the sarcolemma are the most frequent. The inherited causes are: metabolic with failure of energy production, including mitochondrial fatty acid ß-oxidation defects, LPIN1 mutations, inborn errors of glycogenolysis and glycolysis, more rarely mitochondrial respiratory chain deficiency, purine defects and peroxysomalα-Methylacyl-CoA-racemase defect (AMACR); dystrophinopathies and myopathies; calcic causes with RYR1 mutations; inflammatory with myositis. Irrespective of the cause of rhabdomyolysis, the pathophysiologic events follow a common pathway, the ATP depletion leading to an increased intracellular calcium concentration and necrosis. Most episodes of rhabdomyolysis are triggered by an environmental stress, mostly fever. This condition is associated with two events, elevated temperature and high circulating levels of pro-inflammatory mediators such as cytokines and chemokines. We describe here an example of rhabdomyolysis related to high temperature, aldolase deficiency, in 3 siblings with episodic rhabdomyolysis without hemolytic anemia. Myoglobinuria was always triggered by febrile illnesses. We show that the underlying mechanism involves an exacerbation of aldolase A deficiency at high temperatures that affected myoblasts but not erythrocytes. Thermolability was enhanced in patient myoblasts compared to control. The aldolase A deficiency was rescued by arginine supplementation in vitro. Lipid droplets accumulated in patient myoblasts relative to control and this was increased by cytokines. Lipotoxicity may participate to myolysis. Our results expand the clinical spectrum of aldolase A deficiency to isolated temperature-dependent rhabdomyolysis, and suggest that thermolability may be tissue specific. We also propose a treatment for this severe disease. Some other diseases involved in rhabdomyolysis may implicate pro-inflammatory cytokines and may be proinflammatory diseases.